Root-Zone Cooling in an Arduino-Based NFT Hydroponic System for Enhancing Lowland Strawberry Cultivation - Suhanto, Rhesti Nurlina; Fatwasauri, Icha; Fazri, Dimas Maulana (Teknotan: Jurnal Industri Teknologi Pertanian, 2026)
Strawberry cultivation in lowland tropical regions remains challenging due to high temperatures, which negatively affect root-zone processes, reduce nutrient uptake efficiency, and limit plant growth. This study addresses these limitations by developing a controlled Nutrient Film Technique (NFT) hydroponic system integrated with a water chiller and an Arduino-based monitoring unit to replicate the optimal root-zone temperature (17–20°C) typically found in highland environments. The system regulates three key parameters: nutrient solution temperature, nutrient concentration, and water flow rate, to support the growth of Mencir strawberry plants under lowland conditions. The experimental setup consisted of an NFT system equipped with temperature sensors, TDS sensor, and flow sensor, with real-time monitoring conducted via an Arduino Uno microcontroller. Experimental results show that the cooling system effectively reduced the nutrient solution temperature from 27–28°C to approximately 17°C within 19 minutes and maintained this range through automated thermostat control. Nutrient concentration remained within the recommended range (1260–1540 PPM) with average of 1419 PPM, while the flow rate was maintained at approximately 3.29 L/min. These controlled conditions enabled stable plant growth, with flowering initiated at Day 13 and fruit ripening achieved within 19–20 days after transplanting. This growth duration indicates accelerated reproductive development compared to typical strawberry cultivation under non-controlled lowland conditions. The findings demonstrate that stable root-zone conditions contribute to improved strawberry growth under lowland environments. This research provides a practical engineering approach for extending strawberry cultivation to non-traditional agroecological zones and highlights the potential improvements of integrated environmental control systems in hydroponic agriculture.